TEKNOLOGI PENGOLAHAN KERUPUK SINGKONG RASA BALADO DARI PEMANFAATAN LIMBAH IKAN LELE DUMBO (Clarias gariepinus) DI DESA MOJOREJO BATU JAWA TIMUR - Ernawati Ernawati; Hapsari Titi Palupi; Eko Agus Alfianto (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
Waste fishery products are usually disposed of them so that they become a problem for the environment in the form of foul odor, and environmental aesthetics. The use of waste results can improve their economic value to the method used as the seasoning of cassava crackers. Balado seasoning is ground chili mixed with several other spices then certain types of food are added including anchovies, fish, and others. This people empowerment activity aims to develop an economically independent and competitive trade group in the era of globalization, implement appropriate food processing technology that speeds up business processes and reduces production costs. In addition, it is also to increase creativity in the diversification of processed and utilization of fishery waste. The method used is a survey, approach with the Mojorejo Village Government to synergize activities related to the problem of improving the quality and productivity of cassava crackers, methods of training and counseling for partners and the surrounding community, and ongoing mentoring guidance. Based on the results of the program implementation, it can be concluded that in general the two partners already have the ability to make processed cassava crackers based on a long experience. The training provided can be received by partners and the community based on the results of the satisfaction survey obtained. Both partners were able to utilize the appropriate technology tools provided, as well as an increased understanding of human resource management, financial management, and marketing. Keywords: Balado, Crackers, Catfish, Waste, Cassava